Efficacy and safety of a fixed dose combination tablet of asunaprevir + beclabuvir + daclatasvir for the treatment of Hepatitis C. (11th February 2020) - Zappulo, Emanuela; Scotto, Riccardo; Buonomo, Antonio Riccardo; Maraolo, Alberto Enrico; Pinchera, Biagio; Gentile, Ivan
ABSTRACT: Introduction : Hepatitis C virus (HCV) is estimated to infect approximately 70 million people worldwide. If left untreated, chronic infection can progress to cirrhosis, liver failure or hepatocellular carcinoma. The advent of new direct-acting antivirals (DAA) has revolutionized patients' chances of treatment and viral elimination. Currently, several DAA options are available on the market. Areas covered : This review focuses on the pharmacokinetics, efficacy, tolerability and safety profile of DCV-TRIO, a twice-daily fixed-dose combination of daclatasvir, asunaprevir and beclabuvir approved in Japan for the treatment of genotype 1 HCV infection. Expert opinion : The DCV-TRIO combination achieved good response rates in genotype 1 patients (SVR12 ≥ 95% in naïve subtype 1b), independently from IL28B genotype, cirrhotic status and prior interferon exposure. On the other hand, unsatisfying response rates were reported in DAA-experienced patients and the risk of RAS selection should not be underestimated. Moreover, DCV-TRIO lacks differentiation from its earlier-launched DAA rivals, presents an inconvenient twice-daily dosing schedule and is not recommended in patients with advanced liver and kidney disease. All these drawbacks considerably limit its effective commercial potential. However, it can be a therapeutic option against HCV in tailored approaches according to the needs of different markets across the world. Abbreviations AE: adverse event; ALT: alanine aminotransferase; AST: aspartate aminotransferase; ASV: asunaprevir; AUC: area under the curve; BCRP: Breast Cancer Resistance Protein; BCV: boceprevir; BID: bis in die; CI: confidence intervals; CLcr: creatinine clearance; DAA: direct acting antivirals; DCV: daclatasvir; EC50: Half maximal effective concentration; GT: genotype; HCV: Hepatitis C virus; IFN: Interferon; NHL: non-Hodgkin lymphoma; OATP: Organic anion transporting polypeptides; OR: odds ratio; P-gp: P-glycoprotein; PK: pharmacokinetics; QD: quo die; RAS: resistance-associated substitutions; SVR: sustained virological response; USD: Unites States dollar